Investigation and design of vibration compensation for a manual wheelchair - Muhamad Hafiz Brahim (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
When traveling over uneven surfaces such as paved road and obstacles, wheelchairs experienced vibration that causes the body of the person who sit on the wheelchair to experienced whole body vibration. The effect of the whole body vibration induced health conditions progress slowly and if this vibration is continuity, the pain may develop into an injury or disease. The objective of this project is to investigate current mechanism used for compensating vibration in a manual wheelchair.